The - edited by Alfred Dupont Chandler; Peter Hagstrom; Orjan Solvell (Oxford University Press, 1998)
Business Strategy is becoming increasingly pluralist, drawing on the insights of different disciplines and business practice in different parts of the world. This book brings together the work and ideas of leading international scholars working in the field under three main headings--Technology, Strategy and Organization, and Regions--to explore from different perspectives the dynamic interplay between the technology of a firm; its strategies; organizational choices; and issues of place, region, and location. Together, the contributors address the challenge of explaining the long-run competitiveness of firms in an ever more global world. This book will be a benchmark for anybody wanting to keep abreast of leading-edge strategic thinking